Method for improving fatigue stability of memory alloy

Optimizing the microstructure structure of nickel-titanium alloy through the cycle torsion process solves its shortcomings in functional fatigue, significantly improves fatigue resistance and functional stability, and enhances its application potential in solid-state refrigeration technology.

CN119640170APending Publication Date: 2025-03-18INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411818610.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

At present, the attenuation of shape memory alloys in functional fatigue has led to the inability to further develop in actual applications, especially in solid-state refrigeration technology, which is difficult to meet the needs of efficient and environmental protection.

Method used

By introducing a cyclic torsion process, a gradient distribution of grain boundaries and dislocations is created, thereby optimizing the fatigue characteristics of coarse crystal nickel-titanium alloys. The process includes cyclic twisting of memory alloy samples, changing their microstructure structure, and improving the distribution of small angle grain boundaries and dislocation density.

Benefits of technology

It significantly improves the fatigue resistance and functional stability of memory alloys, extends its lifespan, and enhances its application potential in solid-state refrigeration technology while maintaining the elastic-heat effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640170A_ABST
    Figure CN119640170A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional materials, and particularly relates to a method for improving fatigue stability of memory alloy. The microstructure is changed by performing a cyclic torsion process on a memory alloy sample, the torsion angle is set to be 10-20 degrees, the torsion rate is set to be 96-144 degrees s <-1 >, and the torsion angle theta is changed in a sine wave form. The service life of the alloy is prolonged to a small extent after 1000 cycles of cyclic torsion processing, and the fatigue life of the alloy under the stress of peak temperature change is prolonged by about 5 times compared with that of an untwisted sample after 2000 cycles of cyclic torsion processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials and relates to a method for improving the fatigue stability of a memory alloy, and specifically relates to a process for improving the fatigue life of a memory alloy while ensuring a refrigeration temperature under a room temperature environment. Background Art

[0002] In the context of the increasingly prominent energy crisis and environmental problems, it is imperative to pay attention to the solid-state refrigeration technology that generates heat effects by solid-state conversion caused by external environmental field stimulation. According to statistics from the United Nations, about 25% to 30% of the world's electricity is used for various refrigeration equipment such as food preservation, cold chain transportation, air conditioning, etc., and refrigeration consumption accounts for a considerable part of the world's total electricity consumption today (about 20%). It is expected that by 2050, the growing demand for refrigeration will double. However, the mainstream vapor compression cooling technology at this stage exacerbates global warming due to the large amount of harmful gas emissions. Energy and environmental protection are eternal topics in today's era, so environmental damage and unsustainable energy consumption are one of the most important problems facing mankind. Solid-state refrigeration using efficient and environmentally friendly caloric refrigerants is an alternative to vapor compression cooling technology, and this technology has a bright future in energy saving. To this end, researchers have carried out a lot of research work in the field of caloric refrigeration.

[0003] At present, the key step of elasto-caloric cooling is to develop elasto-caloric materials with excellent performance, because most of the research focuses on improving a single cooling index by sacrificing other indexes, and it is very necessary to solve the contradictions between various cooling indexes, but this is extremely challenging. At present, elasto-caloric materials are mainly based on shape memory alloys. Under uniaxial stress driving, due to the endothermic-exothermic nature of the phase change process, the latent heat is released or absorbed during loading or unloading, resulting in temperature changes of the alloy. Among them, among the shape memory alloys that have been widely studied, the nearly equiatomic nickel-titanium alloy is one of the most widely studied and applied shape memory alloys due to its high damping performance, biocompatibility and mechanical properties. However, the attenuation of the alloy in functional fatigue has prevented it from being further applied in practice. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the fatigue stability of memory alloys. In this study, we optimize the fatigue properties of a coarse-grained nickel-titanium alloy by introducing a cyclic torsion process to create a gradient distribution of grain boundaries and dislocations.

[0005] The technical solution of the present invention is as follows:

[0006] A method for improving the fatigue stability of a memory alloy. The microstructure is changed by performing a cyclic torsion process on a memory alloy sample; the cyclic torsion process is as follows: fix one end of the sample, and perform cyclic torsion of the other end around the central axis of the sample with a torsion angle of θ, rotate clockwise by θ-rotate counterclockwise by θ to return to the original position-rotate counterclockwise by θ-rotate clockwise by θ to return to the original position, the above process is one cycle of cyclic torsion, and the torsion cycle is greater than 2; or, perform cyclic torsion of the two ends of the sample around the central axis of the sample with a torsion angle of θ / 2 in opposite directions at the same time, and twist the two ends of the sample in opposite directions by θ / 2 at the same time-return to the original position-reverse the direction of the two ends of the sample (change from clockwise rotation by θ / 2 to counterclockwise rotation by θ / 2, or from counterclockwise rotation by θ / 2 to clockwise rotation by θ / 2) and twist in opposite directions by θ / 2 at the same time-return to the original position, the above process is one cycle of cyclic torsion, and the torsion cycle is greater than 2.

[0007] Furthermore, in the cyclic torsion process, the torsion angle θ (amplitude) is 10° to 20°.

[0008] Furthermore, in the cyclic torsion process, the torsion rate is 96°s -1 ~144°s -1 , the torsion angle θ changes in the form of a sine wave.

[0009] Furthermore, in the cyclic torsion process, the torsion cycles are 1000 to 3000, preferably 1500 to 2500.

[0010] Furthermore, the memory alloy sample is a nickel-titanium alloy, and the preparation method is: measuring titanium and nickel elements in a container, vacuum melting to obtain a nickel-titanium alloy plate; thinning and hot-rolling the alloy plate at high temperature, and processing it into a rod-shaped tensile sample.

[0011] Furthermore, the molar content of nickel in the nickel-titanium alloy is 40-60%; the vacuum degree is 10 -3 ~10 -4 Pa; the high temperature is 800-1000°C.

[0012] Furthermore, the sample size of the rod-shaped tensile sample after cyclic torsion processing is: axial length of 10 to 30 mm, and diameter of 3 to 6 mm.

[0013] The advantages and beneficial technical effects of the present invention are as follows:

[0014] 1. The microstructure of the rod-shaped nickel-titanium alloy changes through the cyclic torsion process of the present invention. The torsion process brings obvious microstructure changes to the edge area: the distribution of small-angle grain boundaries increases, the dislocation density increases, and the two are distributed in a gradient from the edge to the core, which greatly improves the fatigue resistance at the edge of the torsion sample, and improves its functional stability while maintaining the elastic-thermal effect. This discovery provides a new idea for the use of spring-cage materials as a new refrigerant for solid-state refrigeration.

[0015] 2. The life of the nickel-titanium alloy sample was slightly improved after 1000 cycles of cyclic torsion processing, and after 2000 cycles of cyclic torsion processing, the fatigue life of the alloy under the stress of peak temperature change was increased by about 5 times compared with the untwisted sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The specifications and dimensions of the MTS 809.25 tension-torsion fatigue tester and the torsion specimens;

[0017] Figure 2 X-ray diffraction results of twisted and untwisted samples;

[0018] Figure 3 The elastocaloric effects of twisted and untwisted samples are summarized;

[0019] Figure 4 The elastic-thermal cycle stability results of the torsion sample and the untwisted sample under a stress of 600 MPa, wherein Figure (a) is the cyclic stress-strain curve of the untwisted sample, Figure (b) is the cyclic adiabatic temperature change of the untwisted sample, Figure (c) is the cyclic stress-strain curve of the sample torsion 1000 times, Figure (d) is the cyclic adiabatic temperature change of the sample torsion 1000 times, Figure (e) is the cyclic stress-strain curve of the sample torsion 2000 times, Figure (f) is the cyclic adiabatic temperature change of the sample torsion 2000 times, Figure (g) is the cyclic stress-strain curve of the sample torsion 4000 times, and Figure (h) is the cyclic adiabatic temperature change of the sample torsion 4000 times;

[0020] Figure 5 It is a summary diagram of the refrigeration adiabatic temperature change and cycle life of the present invention;

[0021] Figure 6 The microstructure diagram and change law of the untwisted sample, Figure (a) is the cross-section of the rod, Figures (b1-b3) are the grain boundary distribution diagrams at different positions, Figures (c1-c3) are the dislocation density distribution diagrams at different positions, Figure (d) is the summary of the grain boundary proportion, and Figure (e) is the summary of the dislocation density;

[0022] Figure 7To show the microstructure and change law of the sample torsioned for 2000 times, Figure (a) is the cross-section of the rod, Figures (b1-b3) are the grain boundary distribution diagrams at different positions, Figures (c1-c3) are the dislocation density distribution diagrams at different positions, Figure (d) is the summary of the grain boundary proportion, and Figure (e) is the summary of the dislocation density. DETAILED DESCRIPTION

[0023] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0024] The cyclic torsion process described in the embodiment is carried out in a tension-torsion fatigue testing machine, model MTS809.25;

[0025] Phase analysis was tested on a SmartLab Studio II X-ray diffractometer;

[0026] The elastic-thermal effect tensile test and elastic-thermal cycle stability test were conducted on an Instron 8862 universal testing machine equipped with a 2620-601 model extensometer. The temperature changes during the test were recorded by a PT100 platinum resistance wire connected to a paperless recorder. The contact between the probe point and the sample was fixed with Satlon brand cyanoacrylate adhesive to ensure the accuracy of heat transfer. There was no insulating material in the entire test process. In addition, sufficient time (240s to 300s) was left to ensure that the sample returned to ambient temperature before proceeding to the next step.

[0027] The microscopic morphology used as a characterization method was photographed using a SUPRA 35 field emission scanning electron microscope. In order to facilitate imaging, the cross-section of the parallel section of the sample to be tested was electrolytically polished after grinding and polishing: electrolytic polishing was performed for 5 seconds at room temperature with a voltage of 20V and a current of 2A using an electrolyte prepared with perchloric acid and alcohol in a volume ratio of 1:9.

[0028] Example 1

[0029] As a basic embodiment of the present invention, the present invention includes a method for improving the fatigue stability of a memory alloy, comprising the following steps:

[0030] First, prepare the nickel-titanium alloy sample

[0031] (1) 2.15 kg of 99.9% high-purity titanium (Ti) particles and 2.72 kg of 99.9% high-purity nickel (Ni) particles were weighed, the oxide layer was removed and placed in a copper crucible of a vacuum arc melting furnace, and the gas was washed three times and then finely extracted to 1×10 -4 Pa vacuum degree and then melted to obtain a larger alloy plate.

[0032] (2) The alloy plate is forged at a high temperature of 850°C to a thickness of 40 mm, and then the plate is repeatedly rolled at 850°C to gradually reduce the thickness from 40 mm to 20 mm to 13 mm to 10 mm, and then pickled to obtain the slab, which is then cut into hot-rolled plates with a size of 500 × 150 × 10 mm.

[0033] (3) The hot-rolled plate is cut into a cylindrical rod using a lathe. The clamping section is φ8*25mm, the parallel section, i.e. the section to be twisted, is φ4.5*20mm (20mm is the axial length), and the connecting part is a chamfer of R3 (see Figure 1 ), cut off 1mm thick arches on both sides of the clamping part, process the end faces to facilitate twisting clamping, and polish the parallel parts to give them a metallic luster.

[0034] The rod-shaped sample was subjected to 1000 cycles of cyclic torsion processing. The specific operation process is as follows: Operation equipment see Figure 1 The sample fixture clamps both ends of the sample, fixes the upper chuck, and realizes the torsion processing by twisting the lower chuck. The lower end of the fixture rotates 15° clockwise around the central axis of the rod-shaped sample - 15° counterclockwise and returns to the origin - 15° counterclockwise - 15° clockwise and returns to the origin. The above torsion process is one cycle, and the change of the torsion angle is in the form of a sine wave. The torsion speed is 144° / s, the torque is ±7.5Nm, and the torsion is cyclically twisted 1000 times according to the above torsion processing method. The obtained sample is recorded as T1000.

[0035] Example 2

[0036] The preparation process is the same as in Example 1, the only difference being that the number of cyclic torsion cycles is 2000, and the obtained sample is recorded as T2000.

[0037] Comparative Example 1

[0038] The preparation process is the same as that in Example 1, the only difference being that there is no cyclic torsion processing process, that is, the number of cyclic torsion cycles is 0, and the obtained sample is recorded as T0.

[0039] Comparative Example 2

[0040] The preparation process is the same as in Example 1, the only difference being that the number of cyclic torsion cycles is 4000, and the obtained sample is recorded as T4000.

[0041] The samples in the above examples and comparative examples were subjected to X-ray diffraction analysis. The results are as follows: Figure 2 As shown, it indicates that the torsion process does not change the phase structure of the alloy.

[0042] Application Example 1

[0043] Elastic thermal effect test

[0044] The rod-shaped samples obtained in the examples and comparative examples were subjected to an elastic-thermal effect test. The specific operation process was as follows: a tensile test was performed under uniaxial stress, the magnitude of the uniaxial stress was changed to cause different degrees of strain in the sample, the sample was connected to a paperless recorder using a platinum resistance wire, and the temperature change under different strains was recorded. During the experiment, a heat exchange time of 300s was set after the stress loading program of different strain amounts to ensure the accuracy of subsequent experimental results.

[0045] Test results see Figure 3 The positive direction of the Y-axis represents the stress loading process, the sample material is stretched, which is manifested as heat release and temperature increase; the negative direction of the Y-axis represents the stress unloading process, the sample material is compressed, which is manifested as heat absorption and temperature decrease.

[0046] The test results of Example 1 are as follows: the adiabatic temperature change results of the sample twisted 1000 times under different strains are as follows: a temperature span of 2K is measured for a strain of 0.8% (the temperature span is the difference between the maximum exothermic temperature change and the endothermic temperature change caused by the stress amplitude), a temperature span of 10.1K is measured for a strain of 1.6%, a temperature span of 14.4K is measured for a strain of 2.4%, a temperature span of 17K is measured for a strain of 3.1%, a temperature span of 22.5K is measured for a strain of 4.5%, a temperature span of 20.9K is measured for a strain of 5.4%, and a temperature span of 19.2K is measured for a strain of 5.9%.

[0047] The test results of Example 2 are as follows: the adiabatic temperature change results of the sample twisted 2000 times under different strains are as follows: a temperature span of 2.2K is measured for a strain of 0.8%, a temperature span of 7.3K is measured for a strain of 1.5%, a temperature span of 13.7K is measured for a strain of 2.3%, a temperature span of 18.1K is measured for a strain of 3.1%, a temperature span of 20.6K is measured for a strain of 4.3%, a temperature span of 18.7K is measured for a strain of 5.4%, and a temperature span of 16.4K is measured for a strain of 6%.

[0048] The test results of Comparative Example 1 are as follows: the adiabatic temperature change results of the sample torsionally twisted 0 times under different strains are as follows: a temperature span of 1.7K is measured for a strain of 0.7%, a temperature span of 8.6K is measured for a strain of 1.5%, a temperature span of 12.8K is measured for a strain of 2.1%, a temperature span of 18.8K is measured for a strain of 3.1%, a temperature span of 25.3K is measured for a strain of 4.5%, a temperature span of 23.1K is measured for a strain of 5.4%, and a temperature span of 20.2K is measured for a strain of 6%.

[0049] The test results of Comparative Example 2 are as follows: the adiabatic temperature change results of the sample torsionally twisted 4000 times under different strains are as follows: 1% strain measured a temperature span of 2.9K, 1.7% strain measured a temperature span of 9.6K, 2.3% strain measured a temperature span of 13K, 3.1% strain measured a temperature span of 16.7K, 4.5% strain measured a temperature span of 23.7K, 5.6% strain measured a temperature span of 23K, and 6% strain measured a temperature span of 16.8K.

[0050] From the above results, it can be seen that the elastic-caloric effect of the samples after different cycles of cyclic torsion has not caused obvious attenuation. The reason why the temperature change decreases instead of increasing when the strain reaches a certain value in the figure is the influence of irreversible strain, that is, in the process of stress-driven martensitic phase transformation, austenite is loaded to transform martensite, and the martensite is not completely transformed into austenite during the unloading process, which manifests as residual strain, resulting in a decrease in the temperature change result during the next loading and unloading process.

[0051] Application Example 2

[0052] Thermal cycling stability test

[0053] The rod-shaped samples obtained in the examples and comparative examples were subjected to elastic-thermal cycle stability tests. The specific operation process was as follows: a tensile fatigue test was performed under a uniaxial stress of 600 MPa, and the samples were connected to a paperless recorder using a platinum resistance wire to record temperature changes. In order to improve the efficiency and continuity of the experiment, 5 sets of temperature change data were recorded every 100 sets of cycles and kept for 240 seconds after loading and unloading to ensure that the temperature returned to room temperature before proceeding to the next procedure.

[0054] Test results see Figure 4 and Figure 5

[0055] The test results of Example 1 are as follows: the temperature change results of the sample twisted 1000 times in the cyclic test at 600 MPa are from -8.1K to -7.5K for 1 to 5 cycles, stabilized at -7.7K for 101 to 105 cycles, stabilized at -7.5K for 201 to 205 cycles, stabilized at -7.4K for 301 to 305 cycles, and finally the sample broke during 386 cycles.

[0056] The test results of Example 2 are as follows: the temperature change results of the sample subjected to 2000 cycles of torsion under 600 MPa in the cycle test are as follows: the temperature change results of the 1-5 cycles are from -8.5K to -7.3K, the temperature change results of the 101-105 cycles are stable at -7.3K, the temperature change results of the 201-205 cycles are stable at -7.8K, the temperature change results of the 301-305 cycles are stable at -7.9K, the temperature change results of the 401-405 cycles are stable at -7.4K, and the temperature change results of the 501-505 cycles are stable at -7. The temperature change results of the 601-605 cycles were stable at -7.2K, the temperature change results of the 701-705 cycles were stable at -7.5K, the temperature change results of the 801-805 cycles were stable at -8K, the temperature change results of the 901-905 cycles were stable at -8.3K, the temperature change results of the 1001-1005 cycles were stable at -7.8K, the temperature change results of the 1101-1105 cycles were stable at -8.3K, and finally the sample broke during the 1114th cycle.

[0057] The test results of Comparative Example 1 are as follows: the temperature change results of the sample with 0 torsion cycles in the cyclic test under 600 MPa are from -10.7K to -6.8K for 1 to 5 cycles, stable at -6.7K for 101 to 105 cycles, stable at -6.7K for 201 to 205 cycles, and finally the sample breaks during 285 cycles.

[0058] The test results of comparative example 2 are as follows: the sample twisted 4000 times in the cyclic test at 600 MPa has an endothermic temperature change result of from -9.6K to -8.1K in the 1st to 5th cycle, and is stabilized at -9.5K in the 101st to 105th cycle. Finally, the sample breaks during 130 cycles.

[0059] Depend on Figure 5 It can be seen that the life of the alloy is slightly improved after 1000 cycles of twisting, and the fatigue life of the alloy under the peak temperature change stress after 2000 cycles is about 5 times higher than that of the untwisted sample. The samples in Comparative Example 1 and Example 2 were analyzed by scanning electron microscope, and it can be seen that Figure 6 and Figure 7 The middle cross section of the sample was selected for the test, and three points in between were selected for microstructural analysis. The grain boundaries and dislocations of the sample were evenly distributed before torsion, while 2000 cycles of torsion brought obvious microstructural changes to the edge area: the distribution of small-angle grain boundaries increased, the proportion of the edge area increased by nearly 60%, and the dislocation density increased significantly, with the edge density increasing from 0.23×10 14 / m 2 Increased to 0.88×10 14 / m 2, and both show a gradient distribution from the edge to the core. When the dislocations carried by the resident slip band can continuously pass through the grain boundary, the small-angle grain boundary will not initiate fatigue cracks at the grain boundary; most large-angle grain boundaries, due to the pile-up of dislocations, will experience fatigue cracking along the grain boundary, and the gradient necessary dislocations and dislocation accumulation induced by large plastic deformation will lead to additional strengthening. This synergistic effect increases the fatigue life of the alloy under the stress of peak temperature change by about 5 times.

[0060] But the more torsion cycles, the better the effect. We also tested alloy samples that were torsioned for 4,000 cycles. Due to the large plastic deformation, the accumulation of dislocations reduced the fatigue life. Among them, the temperature change of samples under different conditions in the fatigue test process was attenuated during the first few cycles of loading and unloading, which is consistent with the result that the functional fatigue of nickel-titanium alloy is not good. We improved this shortcoming through the gradient distribution of grain boundaries and dislocations through the cyclic torsion process. The temperature change remained stable in the subsequent fatigue test because the dislocations formed in the previous cycle suppressed the formation of subsequent dislocations, which was manifested as a nearly linear stress-strain curve result.

[0061] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the fatigue stability of memory alloy, characterized in that: The microstructure is changed by performing a cyclic torsion process on the memory alloy sample; the cyclic torsion process is as follows: fix one end of the sample, and perform a cyclic torsion of the other end around the central axis of the sample with a torsion angle of θ, rotate clockwise θ-counterclockwise θ to return to the original position-counterclockwise θ-clockwise θ to return to the original position, the above process is a cycle of cyclic torsion, and the torsion cycle is greater than 2; Or, both ends of the sample are simultaneously twisted in opposite directions around the sample center axis with a torsion angle of θ / 2, both ends of the sample are simultaneously twisted in opposite directions by θ / 2 - return to the original position - both ends of the sample are respectively reversed in direction (from clockwise rotation of θ / 2 to counterclockwise rotation of θ / 2, or from counterclockwise rotation of θ / 2 to clockwise rotation of θ / 2) and then twisted in opposite directions by θ / 2 - return to the original position, the above process is one cycle of cyclic torsion, and the number of twisting cycles is greater than 2.

2. The method according to claim 1, characterized in that: In the cyclic twisting process, the twisting angle θ (amplitude) is 10° to 20°.

3. The method according to claim 1, characterized in that: In the cyclic torsion process, the torsion rate is 96°s -1 ~144°s -1 , the torsion angle θ changes in the form of a sine wave.

4. The method according to claim 1, characterized in that: In the cyclic twisting process, the twisting cycles are 1000 to 3000, preferably 1500 to 2500.

5. The method according to claim 1, characterized in that: The memory alloy sample is a nickel-titanium alloy, and the preparation method is as follows: titanium and nickel are measured in a container, and vacuum smelted to obtain a nickel-titanium alloy plate; the alloy plate is thinned and hot-rolled at a high temperature, and then processed into a rod-shaped tensile sample.

6. The method according to claim 5, characterized in that: The molar content of nickel in the nickel-titanium alloy is 40-60%; the vacuum degree is 10 -3 ~10 -4 Pa; the high temperature is 800-1000°C.

7. The method according to claim 5, characterized in that: The sample size of the rod-shaped tensile sample after cyclic torsion processing is: axial length is 10-30mm, and diameter is 3-6mm.